"Bring history alive" : exploring the evolution of Flying Apsaras in Mogao Caves : a thesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, Wellington, New Zealand - Dai, Xinyue (Massey University, 2019)
This research project explores a visualisation framework with an educational purpose for digital heritage, by using a digital story-telling format. It examines a visualisation that demonstrates the historical evolution of the flying Apsaras - one of the main characters of ancient grottoes in Mogao caves, located in Dunhuang province, China. Culture and religion merged in Dunhuang, an ancient city in the middle of the Silk Road. Dunhuang was influenced by multiple cultures - from the West and East, and it was in this context that the Mogao Caves was established. On the wall paintings, the flying Apsara was a vehicle through which cultural changes in a thousand years were shown, through changes in their appearance. Now due to the environmental problem and over-visiting of the Mogao Caves, visitors can only explore a limited number of caves and have difficulty understanding the stories in the faded and incomplete murals. This project thus examines art style transformation of the murals, extracted representative symbols, and patterns and colour sets of each dynasty reinterpreted in a digital narrative with a modern aesthetic. The methodologies used in this project encompassed historical analysis, character design, and experience design that includes information design. The design output provides an accessible framework for other designers engaging with a digital heritage like the Mogao Caves. Also, by extending this project, potential functionalities of digital narrative could be explored for educational purpose.
Figures 1, 3, 9 & 10 have been removed for copyright reasons, but Figures 7 & 8 remain owing to inaccessibility. Figure 1 can be found in Demas, 2017, p. 8 (Figure 1.6) https://link-springer-com.ezproxy.massey.ac.nz/content/pdf/10.1007%2F978-3-319-09000-9_1.pdf, Figure 3 in Digital Dunhuang, Cave 285 https://www.e-dunhuang.com/cave/10.0001/0001.0001.0285, Figure 9 in Kenderdine, 2013, p. 200 (Photo 1) doi:10.1111/cura.12020, & Figure 10 in Kenderdine, 2013, p. 213 (Photo 11) doi:10.1111/cura.12020
Keywords: Digital storytelling; Instructional systems|; Design; Characters and characteristics in art; Interpretation of cultural and natural resources; Mural painting and decoration, Buddhist; China; Dunhuang Caves; Sustainable tourism; Flying Apsaras; digital storytelling; experience design; character design; digital heritage; Mogao Caves